Basic of Artificial Neural Network - Sehrawat, Mr Rahul; Gupta, Mr Pankaj; Yadav, Mr Ravishu (IJRDO -Journal of Computer Science Engineering, 2015)
An Artificial Neural Network (ANN) is an information processing paradigm that is inspired by the way biologicalnervous systems, such as the brain, process information. The key element of this paradigm is the novel structure of theinformation processing system. It is composed of a large number of highly interconnected processing elements (neurons)working in unison to solve specific problems. Artificial neural networks are generally presented as systems of interconnectedneurons which can compute values from inputs, and are capable of machine learning as well as pattern recognition thanks totheir adaptive nature. ANNs, like people, learn by example. Learning in biological systems involves adjustments to the synapticconnections that exist between the neurons. This is true of ANNs as well. This paper gives overview of Artificial NeuralNetwork, working & training of ANN. It also explain the application and advantages of ANN.